درجة النضج المهني لدى المتربصين في مراكز التكوين المهني حسب نمط التمهين. -دراسة ميدانية على مستوى بعض مراكز التكوين المهني بمدينتي المسيلة وأولاد دراج- - صواش عيسى; لالي عثمان; اشراف: واضح العمري (جامعة محمد بوضياف -المسيلة, 2025)
استهدف البحث معرفة درجة النضج المهني لدى عينة من المتربصين في التكوين المهني حسب نمط التمهين ببعض مراكز التكوين المهني لولاية المسيلة، وقد استخدم الباحثان المنهج الوصفي في دراسة إشكالية البحث، والأداة تمثلت في مقياس النضج المهني المصمم من قبل حمدان السواط، وتم توزيعه على عينة عشوائية بسيطة حجمها 100 طالب متربص خلال الموسم 2023/2024، وقد توصل البحث إلى نتائج أهمها أن أفراد العينة يملكون درجة مرتفعة من النضج المهني، إضافة إلى وجود فروق ذات دلالة إحصائية في درجة النضج المهني تعزى لمتغير الجنس ولصالح الإناث وفروق حسب متغير المستوى الدراسي لصالح المستويات الأعلى. الكلمات المفتاحية: النضج المهني- التكوين المهني – المتربصين- التمهين. Abstract: The aim of the research was to identify the degree of vocational maturity of a sample of trainees in vocational training based on the apprenticeship model in certain vocational training centres in the wilaya of M'sila.the descriptive approachwas used to study the research problem, and the instrument was the vocational maturity scale designed by Hamdan Al-Sawat. It was distributed to a simple random of 100 student trainees during the 2023/2024 season. The most important results are that the sample members have a high degree of professional maturity, in addition to the existence of statistically significant differences in the degree of professional maturity due to the gender variable in favour of women, and differences according to the academic level variable in favour of higher levels. Key words: vocational maturity, trainees, apprenticeship, training centres